Asgard: Are NoSQL databases suitable for ephemeral data in serverless workloads? - Shankar, Karthick; Mahgoub, Ashraf; Zhou, Zihan; Priyam, Utkarsh; Chaterji, Somali (Frontiers in High Performance Computing, 2023)
Serverless computing platforms are becoming increasingly popular for data analytics applications due to their low management overhead and granular billing strategies. Such analytics frameworks use a Directed Acyclic Graph (DAG) structure, in which serverless functions, which are fine-grained tasks, are represented as nodes and data-dependencies between the functions are represented as edges. Passing intermediate (ephemeral) data from one function to another has been receiving attention of late, with works proposing various storage systems and methods of optimization for them. The state-of-practice method is to pass the ephemeral data through remote storage, either disk-based (e.g., Amazon S3), which is slow, or memory-based (e.g., ElastiCache Redis), which is expensive. Despite the potential of some prominent NoSQL databases, like Apache Cassandra and ScyllaDB, which utilize both memory and disk, prevailing opinions suggest they are ill-suited for ephemeral data, being tailored more for long-term storage. In our study, titled Asgard, we rigorously examine this assumption. Using Amazon Web Services (AWS) as a testbed with two popular serverless applications, we explore scenarios like fanout and varying workloads, gauging the performance benefits of configuring NoSQL databases in a DAG-aware way. Surprisingly, we found that, per end-to-end latency normalized by $ cost, Apache Cassandra's default setup surpassed Redis by up to 326% and S3 by up to 189%. When optimized with Asgard, Cassandra outdid its own default configuration by up to 47%. This underscores specific instances where NoSQL databases can outshine the current state-of-practice.